2022
DOI: 10.3393/ac.2021.01004.0143
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment inflammatory markers predicting treatment outcomes in colorectal cancer

Abstract: We aimed to review whether pretreatment inflammatory markers reflect the short- and long-term outcomes of patients with colon cancer, rectal cancer, colon and rectal cancers, and metastatic colorectal cancer (CRC). We found that pretreatment complete blood count and blood chemistry tests reflect short-term and long-term oncological outcomes in patients with CRC. Specifically, in patients with colon cancer, hypoalbuminemia was associated with worse postoperative morbidity, mortality, and inferior survival. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…The multivariable analysis showed that prognostic nutritional index was an independent prognostic factor for overall survival, whereas the controlling nutritional status score, neutrophil-to-lymphocyte ratio, lymphocyte-tomonocyte ratio, and platelet-to-lymphocyte ratio were not. The patients were divided into three P-CONUT groups as follows: G1, controlling nutritional status (0-4) and high prognostic nutritional index; G2, controlling nutritional status (0-4) and low prognostic nutritional index; and G3, controlling nutritional status (5)(6)(7)(8)(9)(10)(11)(12) and low prognostic nutritional index. There were significant survival differences between the P-CONUT groups (5-year overall survival of G1, G2, and G3 were 91.7%, 81.2%, and 64.1%, respectively; p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The multivariable analysis showed that prognostic nutritional index was an independent prognostic factor for overall survival, whereas the controlling nutritional status score, neutrophil-to-lymphocyte ratio, lymphocyte-tomonocyte ratio, and platelet-to-lymphocyte ratio were not. The patients were divided into three P-CONUT groups as follows: G1, controlling nutritional status (0-4) and high prognostic nutritional index; G2, controlling nutritional status (0-4) and low prognostic nutritional index; and G3, controlling nutritional status (5)(6)(7)(8)(9)(10)(11)(12) and low prognostic nutritional index. There were significant survival differences between the P-CONUT groups (5-year overall survival of G1, G2, and G3 were 91.7%, 81.2%, and 64.1%, respectively; p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The CONUT score was calculated using serum albumin (g/dL), total lymphocyte (count/mm 3 ), and total cholesterol (mg/dL) levels (Supplementary Table S1). In our study, the patients were divided into low (0-1), intermediate (2)(3)(4), and high (5)(6)(7)(8)(9)(10)(11)(12) CONUT score groups as previously described (5). PNI was calculated as 10 × serum albumin (g/dL) + 0.005 × total peripheral lymphocyte count (mL).…”
Section: Calculations Of Conut Score and Pnimentioning
confidence: 99%
See 2 more Smart Citations
“…It was also determined to be an independent prognostic factor for mCC patients [25]. In multiple studies, hypoalbuminemia was associated with poor OS in mCC and poor disease-free survival in colon cancer patients undergoing surgery [26][27][28]. In multiple studies, the monocyte count in different prognostic markers was associated with OS in mCC patients [29,30].…”
Section: Discussionmentioning
confidence: 99%